ANALISIS PENGUKURAN KINERJA PENGELOLAAN KEUANGAN DAERAH KABUPATEN GRESIK TAHUN ANGGARAN 2009-2013 - Habibah, Nur (Jurnal Akuntansi AKUNESA, 2014)
This research is aimed to analyze financial working performance of Gresik District in Fiscal Year 2009-2013. The research method used is qualitative descriptive and used secondary data obtained from primary sources. The result of this research conclude that independence ratio is 37,26%, it means quite independent of the interest of local finance used own local revenues received. Dependence ratio of Gresik Districtin Fiscal Year 2009-2013 show the average amount 56,02%, it mean ?Very High?. Fiscal decentralization ratio of Gresik District in Fiscal Year 2009-2013 show the average amount 22,38%, it mean ?medium?. Effectivity ratio of local revenues have a tendency ?very effective? with effectivity level 102,32%. Efficiency ratio of revenues Gresik District in Fiscal Year 2009-2013 have a tendency ?Less Efficient?, with efficiency level 97,45%. Own local revenue was growth, but own local revenue was growth declined from 2009 to 2013. Whereas in 2010 decreased by 0,29%.Keyword : Gresik District, measurement of financial working performance, regional financial ratio, targets and realization report of APBD.Abstraksi